2004
DOI: 10.1002/mar.20007
|View full text |Cite
|
Sign up to set email alerts
|

A nonverbal test of naturalistic memory for alcohol commercials

Abstract: This study investigated some of the most important properties of a nonverbal test of memory for alcohol commercials. Nonverbal tests may be important for a wide range of applied research questions. Several distinct streams of basic and advertising-related research provide justification for more research on this class of test in consumer and applied health research. These lines of research also suggest ways to improve applications and assessments, as implemented in the present study. Improving assessments and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Media exposure to others using drugs and alcohol is a significant risk for substance use (Villani, 2001). Implicit memory measures may be useful in identifying the nature of the changes that result from social learning before actual substance use begins (e.g., messages in popular media; Fleming et al, 2004;Stacy et al, 2004). One effective campaign to reduce teen smoking involved portrayals of cigarette manufacturers as manipulators (Goldman & Glantz, 1998).…”
Section: Cognitive Inoculation Trainingmentioning
confidence: 99%
“…Media exposure to others using drugs and alcohol is a significant risk for substance use (Villani, 2001). Implicit memory measures may be useful in identifying the nature of the changes that result from social learning before actual substance use begins (e.g., messages in popular media; Fleming et al, 2004;Stacy et al, 2004). One effective campaign to reduce teen smoking involved portrayals of cigarette manufacturers as manipulators (Goldman & Glantz, 1998).…”
Section: Cognitive Inoculation Trainingmentioning
confidence: 99%
“…This is because the response format leads to self-generation of responses that could be almost anyth.ing-a potentially vast set size (Nelson et al, 1998) or "fan" (Anderson, 1983) of alternatives. The importance of relative cognition and alternatives is emphasized in areas as diverse as advertising (Stacy, Pearce, et al, 2004;Stewart, 1989), traditional social learning theory (Rotter, 1954}, and motivational theory (Cox et al , Chapter 17;Palfai, Chapter 26}. Further, a number of models of memory instantiate memory competition, whether conceived of as an automatic o r explicit form of memory.…”
Section: Relative Cognitionmentioning
confidence: 99%
“…Portrayals of alcohol in the media have been linked to the development and maintenance of beliefs about and attitudes toward alcohol. Some studies have shown, for instance, that young people who are more exposed to positive alcohol portrayals and advertising have more favorable beliefs about drinking, say they are more likely to drink in the future, and are more likely to consume alcohol (Grube and Wallack 1994; Snyder et al 2006; Stacy et al 2004). Alcohol portrayals in the content of television programs also reinforce existing alcoholic behaviors.…”
mentioning
confidence: 99%